2015
DOI: 10.1039/c5ra14590b
|View full text |Cite
|
Sign up to set email alerts
|

Conducting poly(o-anisidine-co-o-phenyldiammine) nanorod dispersed epoxy composite coatings: synthesis, characterization and corrosion protective performance

Abstract: Conducing polymers (CPs) have been significantly contributing to the development of high performance new-generation anti-corrosive coatings. CPs nanofiller dispersed insulating polymer coating effectively prevents the transport of corrosive ions (H + , O 2-, Cl -, OHetc) at coating-metal interface, via barrier or redox mechanism. In view of this, for the first time, we report the synthesis of poly (o-anisidine-co-o-phenyldiammine) P(oA-co-oPDA) copolymer conducting nanorods. Poly (o-anisidine) (PoA) conducting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Figure presents the FTIR spectra of the copolymer, IWP, and COIW. The FTIR spectrum of the copolymer (Figure A) shows the characteristic bands of the poly(aniline‐ co ‐anisidine) . The N─H and C═N stretching vibrations appeared at 3403 and 1622 cm −1 , respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure presents the FTIR spectra of the copolymer, IWP, and COIW. The FTIR spectrum of the copolymer (Figure A) shows the characteristic bands of the poly(aniline‐ co ‐anisidine) . The N─H and C═N stretching vibrations appeared at 3403 and 1622 cm −1 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1A) shows the characteristic bands of the poly(aniline-coanisidine). [25][26][27] The N─H and C═N stretching vibrations appeared at 3403 and 1622 cm −1 , respectively. C═C stretching bands for the quinonoid rings observed at 1564 cm −1 and those for benzenoid groups emerged at 1506 and 1457 cm −1 .…”
Section: Electrochemical Measurementmentioning
confidence: 99%
“…This indicates that the protection performance of the WSA-PMF-80 gets reduced after the continuous immersion of 48 h. However, a negligible increase in fb was recorded at high frequency range after 216 h. This further implies that the nanocomposite coatings show no delamination under saline medium even after a longer exposure time . These studies revealed that the proposed nanocomposite coatings possess reasonably higher corrosion potential ( E corr = −0.191 V) and impedance values ( Z = 10 7 Ohm cm 2 ) than the other oleo polymer composites ( E corr = −0.533 to 0.314 V and Z = 10 3 to 10 5 Ohm cm 2 ) and these values are comparable to some of the commercial epoxy and polyurethane ( Z = 10 7 Ohm cm 2 ) coatings. , …”
Section: Resultsmentioning
confidence: 99%
“…67 These studies revealed that the proposed nanocomposite coatings possess reasonably higher corrosion potential (E corr = −0.191 V) and impedance values (Z = 10 7 Ohm cm 2 ) than the other oleo polymer composites (E corr = −0.533 to 0.314 V and Z = 10 3 to 10 5 Ohm cm 2 ) and these values are comparable to some of the commercial epoxy and polyurethane (Z = 10 7 Ohm cm 2 ) coatings. 24,68 Salt Spray Test. The salt spray test was performed in 5.0 wt % NaCl solution under 90% humid environment for 360 h (Figure S6) to analyze the corrosion protection efficiency of WSA-PMF-80 and WSA-PMF-80-RGO-x nanocomposite coatings.…”
Section: Acs Sustainable Chemistry and Engineeringmentioning
confidence: 99%
“…Nanocomposite coatings have demonstrated improved physico‐mechanical characteristics and even distribution of nanostructures within the epoxy matrix. It exhibited outstanding corrosion resistance properties as compare to other coatings 119 …”
Section: Poa Derivativesmentioning
confidence: 99%